Cardiac pathology in death from electrocution - Fineschi, Vittorio; Karch, Steven B.; D'Errico, Stefano; Pomara, Cristoforo; Riezzo, Irene; Turillazzi, Emanuela (International journal of legal medicine, 2006)
To better characterize the morphologic changes in electrocution, morphologic changes in the hearts of 21 subjects, who died instantaneously of electrocution, were compared to the hearts of decedents with different types of death. Sixteen myocardial samples per heart were processed for histological examination, and sections were prepared with a variety of specific stains. The frequency, location and extent of myocellular segmentation (stretching and/or rupture) of intercalated discs and associated changes of myocardial bundles and single myocells [myofibre break-up (MFB)] were recorded, quantitatively analysed and statistically evaluated. The frequency of MFB was maximal in cases of electrocution (90%). The findings show that MFB is an ante-mortem change and may be a distinct finding in electrocution.